Augmented Reality Applications for Enhancing Environmental Awareness in Smart Tourism: A Systematic Literature Review - Victor Marudut Mulia Siregar; Andi Setiadi Manalu; Roy Sahputra Saragih (Institute of Computer Science (IOCS), 2026)
Augmented Reality (AR) has been increasingly adopted in smart tourism to enhance visitor experiences and support sustainability-oriented learning. However, empirical evidence regarding how AR applications contribute to environmental awareness and sustainable tourism practices remains fragmented and insufficiently synthesized. This study conducts a systematic literature review to examine the role of AR in enhancing environmental awareness within smart tourism contexts and its potential contribution to sustainability-oriented tourism development. The review addresses three research questions concerning the implementation of AR applications for environmental learning, the comparative effectiveness of AR and non-AR approaches, and the key challenges and research opportunities associated with AR in sustainability-oriented tourism. The review follows the PICOC framework (Population, Intervention, Comparison, Outcome, Context) and PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. A structured search of the Scopus database covering publications from 2022 to 2025 resulted in 32 empirical journal articles included in the final analysis. The findings indicate that AR applications, such as mobile AR systems, location-based interpretation, immersive environmental visualization, and gamified learning tools, are widely implemented in tourism environments including museums, heritage sites, geotourism destinations, natural parks, and wildlife attractions. Overall, AR tends to enhance environmental understanding, emotional engagement, and pro-environmental intentions more effectively than conventional interpretation media. These outcomes contribute to strengthening visitor awareness of environmental conservation and responsible tourism behavior. This review synthesizes fragmented empirical evidence and highlights key methodological and technological gaps while outlining future research directions for advancing AR-based environmental learning and sustainability practices within smart tourism ecosystems.